2001
DOI: 10.1007/s002160100852
|View full text |Cite
|
Sign up to set email alerts
|

Self-absorption effects in radially and axially viewed inductively coupled plasma-atomic emission spectrometry - the key role of the operating conditions

Abstract: Self-absorption effects leading to curvatures of the upper part of calibration graphs were investigated in multichannel detection ICP-AES. A dual view Optima 3000 ICP system was used to enable the simultaneous determination of 38 lines for both radial and axial viewing. Resonance and non-resonance lines were selected for both atomic and ionic lines. The concentrations of 22 standards were in the range 0.1-100 mg L(-1) and two sets of operating conditions, namely power and carrier gas flow rate, were used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Similar self-absorption effects were observed when axially and radially viewed systems were compared, 20 with a better signal-to-noise ratio for the axially viewed equipment. However, self-absorption effects for resonant lines were more evident in the axially viewed system.…”
Section: Figures Of Merit For Icp Oesís With Axially and Radially Viesupporting
confidence: 62%
See 3 more Smart Citations
“…Similar self-absorption effects were observed when axially and radially viewed systems were compared, 20 with a better signal-to-noise ratio for the axially viewed equipment. However, self-absorption effects for resonant lines were more evident in the axially viewed system.…”
Section: Figures Of Merit For Icp Oesís With Axially and Radially Viesupporting
confidence: 62%
“…The authors concluded that the axial mode seemed to have definitive advantages over radial viewing. 20 Similar conclusions were presented when figures of merit of both systems were compared. 70 Axially viewed configuration presented better detection power, even when complex samples were analysed.…”
Section: Figures Of Merit For Icp Oesís With Axially and Radially Viesupporting
confidence: 59%
See 2 more Smart Citations
“…Concentrations higher than 10 mg/l were not used in this work so as to avoid contaminating the nebulization system, however linearity is normally maintained to concentrations above 100 mg/l. Deviations from linearity at high concentration are due to self-absorption [40] in which photons emitted in the center of the plasma are absorbed by unexcited atoms in the cooler outer part of the plasma. Table 2 gives the performance conditions typical of the experiments performed in this work.…”
Section: Fast Electronicsmentioning
confidence: 99%